The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.25186/cs.v13i3.1438
|View full text |Cite
|
Sign up to set email alerts
|

SAPROBIC FUNGI AS BIOCONTROL AGENTS OF HALO BLIGHT (Pseudomonas syringae pv. garcae) IN COFFEE CLONES

Abstract: Halo blight caused by Pseudomonas syringae pv. garcae is a limiting disease in coffee production. There are few efficient commercial products on the market to control this disease, and therefore, the prospection of different biocontrol agents is a promising alternative. The objectives in this study were (i) to select saprobic fungi with the potential to control halo blight in coffee clones, and (ii) to evaluate the contributions of induced resistance as control mechanisms. Plants were sprayed with Gonytrichum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…Phialomyces macrosporus is reported in literature as a potential resistance inducer in coffee plants against Pseudomonas syringae pv. garcae (Botrel et al, 2018) and Colletotrichum gloeosporioides (Rodríguez et al, 2016) and in eucalyptus plants against Puccinia psidii Winter (Pucciniales: Pucciniaceae) (Pierozzi, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phialomyces macrosporus is reported in literature as a potential resistance inducer in coffee plants against Pseudomonas syringae pv. garcae (Botrel et al, 2018) and Colletotrichum gloeosporioides (Rodríguez et al, 2016) and in eucalyptus plants against Puccinia psidii Winter (Pucciniales: Pucciniaceae) (Pierozzi, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A. C. Almeida, Izabel, & Gusmão, 2011;Leão-Ferreira, Pascholati, Gusmão, & Castañeda Ruiz, 2013;Santa Izabel & Gusmão, 2018). Some of these saprobes were being used as potential biological control agents and resistance inducers (Resende, Milagres, Rezende, Aucique-Perez, & Rodrigues, 2015;Barros, Fonseca, Balbi-Peña, Pascholati, & Peitl, 2015;Rodríguez et al, 2016;Peitl et al, 2017;Ribeiro et al, 2018;Botrel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other authors have reported the use of P. macrosporus as a biocontrol agent in coffee diseases. Botrel et al (2018) observed a reduction in the severity of coffee halo blight of up to 72% when the seedlings were previously treated with the fungus P. macrosporus. Rodríguez et al (2016) observed similar results in the control of C. gloeosporioides in coffee seedlings treated with P. macrosporus.…”
Section: Coffee Sciencementioning
confidence: 93%
“…Furthermore, they can withstand sudden variations in temperature and humidity and sustain biological control in such environment, which turn them promising biological control agents (Köhl et al, 1995). Currently, saprobe fungi have been used as a biological agent for coffee disease control (Botrel et al, 2018;Rodríguez et al,2016). Therefore, we hypothesize that saprobe fungi might inhibit C. coffeicola growth in crop residues and its production antifungal compounds and cell-wall degrading enzyme may play a role in the pathogen displacement.…”
Section: Screening Testmentioning
confidence: 99%
“…The potential of saprobic fungi, such as Phialomyces macrosporus, in disease control has been reported against coffee bacterial blight (Pseudomonas syringae pv. garcae), with a 42% reduction in disease severity and a 40% increase in seedling height (Botrel et al 2018).…”
Section: Introductionmentioning
confidence: 99%